Roots of Digamma

Calculus Level 5

a Ψ 1 a 3 = A ζ ( B ) γ C γ π D E \large \sum _{ a\in \Psi }^{ }{ \frac { 1 }{ { a }^{ 3 } } } =-A\zeta \left( B \right) -{ \gamma }^{ C }-\frac { { \gamma \pi }^{ D } }{ E }

The above equation, where Ψ \Psi denotes all the roots of digamma function , holds true for positive integers A A , B B , C C , D D , and E E with B B being an odd integer. Find A + B + C + D + E A+B+C+D+E .

Notation : γ \gamma denotes the Euler-Mascheroni constant , γ 0.5772 \gamma \approx 0.5772 .


The answer is 14.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
Jun 10, 2016

We use the identity F ( z ) = ψ ( z ) Γ ( z ) = e 2 γ z α Ψ ( 1 z α ) e z α , F(z) \; = \; \frac{\psi(z)}{\Gamma(z)} \; = \; -e^{-2\gamma z} \prod_{\alpha \in \Psi} \left(1 - \frac{z}{\alpha}\right)e^{\frac{z}{\alpha}} \;, which is valid for all z C z \in \mathbb{C} , to deduce that F ( z ) F ( ω z ) F ( ω 2 z ) = α Ψ ( 1 z 3 α 3 ) = 1 + ( α Ψ 1 α 3 ) z 3 + F(z)F(\omega z)F(\omega^2z) \; = \; -\prod_{\alpha \in \Psi}\left(1 - \frac{z^3}{\alpha^3}\right) \; = \; -1 + \left(\sum_{\alpha \in \Psi}\frac{1}{\alpha^3}\right)z^3 + \cdots where ω = e 2 π i 3 \omega = e^{\frac{2\pi i}{3}} is a primitive cube root of unity. Standard results tell us that F ( z ) = 1 2 γ z + 1 4 ( π 2 6 γ 2 ) z 2 1 3 ( 2 γ 3 γ π 2 + 4 ζ ( 3 ) ) z 3 + F(z) \; = \; -1 - 2\gamma z + \tfrac14(\pi^2 - 6\gamma^2)z^2 - \tfrac13\big(2\gamma^3 - \gamma \pi^2 + 4\zeta(3)\big)z^3 + \cdots and hence it is easy to show that F ( z ) F ( ω z ) F ( ω 2 z ) = 1 ( γ 3 + 1 2 γ π 2 + 4 ζ ( 3 ) ) z 3 + F(z)F(\omega z)F(\omega^2 z) \; = \; -1 - \big(\gamma^3 + \tfrac12\gamma \pi^2 + 4\zeta(3)\big)z^3 + \cdots so that α Ψ 1 α 3 = 4 ζ ( 3 ) γ 3 1 2 γ π 2 \sum_{\alpha \in \Psi} \frac{1}{\alpha^3} \; = \; -4\zeta(3) - \gamma^3 - \tfrac12\gamma \pi^2 making the answer 4 + 3 + 3 + 2 + 2 = 14 4 + 3 + 3 + 2 + 2 = \boxed{14} .

How did you calculate the taylor series? I needed WA for that since my method was so tedious.

Julian Poon - 5 years ago

Log in to reply

Calculating the series expansion of Γ ( z ) \Gamma(z) is, as you say, long, and tedious. Wikipedia helpfully gives the explicit expansion up to terms in z 2 z^2 , (exactly what we want!). The series expansion ψ ( z ) = 1 z γ + n = 2 ( 1 ) n ζ ( n ) z n 1 \psi(z) \; = \; -\frac{1}{z} - \gamma + \sum_{n=2}^\infty (-1)^n \zeta(n)z^{n-1} is standard, and putting the two together is straightforward. Even simpler was plugging

Series[PolyGamma[0,z]/Gamma[z],{z,0,3}]

into Mathematica (which I did afterwards!).

If you forced me to do it by hand, I would integrate the formula for ψ ( z ) \psi(z) , obtaining ln Γ ( z ) = ln z γ z + n = 2 ( 1 ) n ζ ( n ) n z n \ln \Gamma(z) \; =\; -\ln z - \gamma z + \sum_{n=2}^\infty (-1)^n \frac{\zeta(n)}{n}z^n (since z Γ ( z ) = Γ ( z + 1 ) z\Gamma(z) = \Gamma(z+1) tends to 1 1 as z 0 z \to 0 , the constant of integration is zero), and hence Γ ( z ) = 1 z e γ z n = 2 e ( 1 ) n 1 n ζ ( n ) z n \Gamma(z) \; = \; \frac{1}{z}e^{-\gamma z} \prod_{n=2}^\infty e^{(-1)^n \frac{1}{n}\zeta(n)z^n} Taking the first two terms of the product and expanding them together with e γ z e^{-\gamma z} will give the expansion of Γ ( z ) \Gamma(z) up to terms in z 2 z^2 .

Mark Hennings - 5 years ago
Aareyan Manzoor
May 28, 2017

before diving into this solution give a read to this . from here we have two easy to derive identities a k 2 = γ 2 + π 2 2 , 1 a k 2 a k z = ψ ( z ) ψ ( z ) + ψ ( z ) + 2 γ z \sum a_k^{-2}= \gamma^2+\dfrac{\pi^2}{2} , \sum \dfrac{1}{a_k^2-a_k z}= \dfrac{-\dfrac{\psi '(z)}{\psi(z)}+\psi(z)+2\gamma}{z} subtracting the first from the second and dividing by z 1 a k 3 a k 2 z = ψ ( z ) ψ ( z ) + ψ ( z ) + 2 γ z ( γ 2 + π 2 2 ) z 2 1 a k 3 = lim z 0 ψ ( z ) ψ ( z ) + ψ ( z ) + 2 γ z ( γ 2 + π 2 2 ) z 2 \sum \dfrac{1}{a_k^3-a_k^2 z}=\dfrac{-\dfrac{\psi '(z)}{\psi(z)}+\psi(z)+2\gamma-z\left( \gamma^2+\dfrac{\pi^2}{2}\right)}{z^2}\\ \sum \dfrac{1}{a_k^3}=\lim_{z\to 0}\dfrac{-\dfrac{\psi '(z)}{\psi(z)}+\psi(z)+2\gamma-z\left( \gamma^2+\dfrac{\pi^2}{2}\right)}{z^2} we can use laurent series(easy to derive by taking deravatives and setting it in the taylor series) ψ ( x ) = 1 x γ + ζ ( 2 ) x ζ ( 3 ) x 2 + O ( x 3 ) \psi(x)=-\dfrac{1}{x}-\gamma+\zeta(2)x-\zeta(3)x^2+O(x^3) to solve the limit. now this is very tedious to do by hand so i used my favourite math engine to just do it all at once. we have or in our case 1 a k 3 = 4 ζ ( 3 ) γ 3 γ π 2 2 \sum \dfrac{1}{a_k^3}= -4\zeta(3)-\gamma^3 -\dfrac{\gamma \pi^2}{2} and the answer follows.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...